Edge computing for Internet of Things: A survey, e-healthcare case study and future direction. (15th August 2019) - Ray, Partha Pratim; Dash, Dinesh; De, Debashis
Abstract: The world has recently witnessed the emergence of huge technological growth in the field of data transmission and smart living through various modes of information and communication technology. For example, edge computing has taken a leading role to embark upon the problems related to the internetwork bandwidth minimization and service latency reduction. Inclusion of small microcontroller chips, smart sensors and actuators in the existing socio-economic sectors have paved the Internet of Things (IoT) to act upon the dissemination of smart services to the end users. Thus, a strong need of understating of the industrial elements of edge computing has become necessary that can share the mutual goal while assimilating with the IoT. This paper advocates the crucial role of industrial standards and elements of the edge computing for the dissemination of overwhelming augmented user experience with conjunction with the IoT. First, we present the taxonomical classification and review the industrial aspects that can benefit from both of the IoT and edge computing scenario, then discuss about each of the taxonomical components in detail. Second, we present two practically implemented use cases that have recently employed the edge-IoT paradigm together to solve urban smart living problems. Third, we propose a novel edge-IoT based architecture for e-healthcare i.e. EH-IoT and developed a demo test-bed. The test results showed promising results towards minimizing dependency over IoT cloud analytics or storage facility. We conclude with discussion on the various parameters such as, architecture, requirement capability, functional issues, and selection criteria, related to the survival of edge-IoT ecosystem incorporation.